COMPARATIVE ANALYSIS OF EFFICACY AND SAFETY OF DIACEREIN VERSUS S-ADENOSYL METHIONINE IN THE MANAGEMENT OF OSTEOARTHRITIS OF KNEE JOINT - R., Gayathri C.; Samuel, Vanitha; Felix, John William; P., Nirmala (International Journal of Current Pharmaceutical Research, 2017)
Objective: Osteoarthritis (OA) the most common type of arthritis is a degenerative joint disease primarily affecting the articular cartilage and its surrounding tissue. Drugs like Diacerein and S-adenosyl methionine (SAMe) are used to remodel the cartilage and slow the progression of the disease, by acting through different mechanisms. Though there is documented evidence of the efficacy of both agents used individually in several clinical trials only a few studies report a comparison. To analyse the efficacy and safety of Diacerein Versus S-adenosyl methionine in the treatment of Osteoarthritis of knee joint. Methods: A prospective randomised interventional study was planned comparing diacerein with SAMe for 12 w in the management of OA of the knee. 40 patients in each group were randomly assigned to receive either diacerein 50 mg twice daily or S-adenosyl methionine 200 mg thrice daily for 12 w. Both groups received a short course of diclofenac 50 mg bd for one week, to tide over the acute symptoms. Results: Assessment of both drugs individually showed an equieffective potential in reducing osteoarthritis pain over a period of 12 w. But the comparison between the two groups showed a marginal improvement in pain relief from the 4th to 12th week of assessment in the diacerein group. Conclusion: Both the drugs for the treatment of OA, were shown to be effective in relieving pain but with a slower onset of action. Since no radiological changes were observed during the 12-week protocol, studies of longer duration are needed to evaluate the long-term effectiveness of these drugs.